Enhancing dosimetric practices through knowledge-based predictive models: a case study on VMAT prostate irradiation - Hadj Henni, Ahmed; Arhoun, Ilias; Boussetta, Amine; Daou, Walid; Marque, Alexandre (Frontiers in Oncology, 2024)
Introduction Acquisition of dosimetric knowledge by radiation therapy planners is a protracted and complex process. This study delves into the impact of empirical predictive models based on the knowledge-based planning (KBP) methodology, aimed at detecting suboptimal results and homogenizing and improving existing practices for prostate cancer. Moreover, the dosimetric effect of implementing these models into routine clinical practice was also assessed. Materials and methods Based on the KBP method, we analyzed 25 prostate treatment plans performed using VMAT by expert operators, aiming to correlate dose indicators with patient geometry. The DavgCav(Gy), V45GyCav(cc), and V15GyCav(cc) of the peritoneal cavity and the V60Gy(%) and V70Gy(%) of the rectum and bladder were linked to geometric characteristics such as the distance from the planning target volume (PTV) to the organs at risk (OAR), the volume of the OAR, or the overlap between the PTV and the OAR. In the second phase, the KBP was used in routine clinical practice in a prospective cohort of 25 patients and compared with the 41 patient plans calculated before implementing the tool. Results Using linear regression, we identified strong geometric predictive factors for the peritoneal cavity, rectum, and bladder (R2 > 0.8), with an average prescribed dose of 97.8%, covering 95% of the target volume. The use of the model led to a significant dose reduction (Δ) for all evaluated OARs. This trend was most notable for ΔV15GyCav=−171.5 cc (p=0.003). Significant reductions were also obtained in average doses to the rectum and bladder, ΔDavgRect= −2.3 Gy (p=0.040), and ΔDavgVess= −3.3 Gy (p=0.039) respectively. Based on this model, we reduced the number of plans with OAR constraints above the clinical recommendations from 19% to 8%. Conclusions The KBP methodology established a robust and personalized predictive model for dose estimation to organs at risk in prostate cancer. Implementing the model resulted in improved sparing of these organs. Notably, it yields a solid foundation for harmonizing dosimetric practices, alerting us to suboptimal results, and improving our knowledge.